PEMANFAATAN CCTV ANALOG CAMERA PADA SISTEM MONITORING KEAMANAN RUANGAN BERBASIS MOBILE WEB - Emanuel Safirman Bata (Universitas Nusa Cendana, 2023)
The greater the diversity of a city, the greater the threat to its security. The number of criminal cases in Kupang City was reported at 1,472, with a crime rate of 438 per 100,000 population. The number of theft cases was 1,288. This is a very high number and if it is not addressed, it will cause unrest in the community. STIKOM Uyelindo Kupang has experienced cases of theft of 7 units of laptops, wallets, helmets. The higher crime rate encourages the need for a technology-based security system that is effective, efficient and easily accessible anywhere, one of which is CCTV. Closed Circuit Television (CCTV) is a digital video camera device and is used to send signals to a monitor screen and aims to increase security. Based on the test results at 24 points of the room and open areas of STIKOM Uyelindo kupang, video streaming can run well on the room security monitoring system and can be accessed publicly.